Synthesis and characterization of YVO4:Eu3+ nanoparticles: kinetics and isotherm studies for the removal of Cd2+ metal ion. Issue 5 (26th January 2016) - Naushad, Mu.; Ansari, Anees A.; ALOthman, Zeid A.; Mittal, Jyoti
Abstract: The prepared YVO4 :Eu 3+ nanoparticle was successfully used for the removal of highly toxic Cd 2+ metal ion. Batch experiments were performed as a function of various experimental parameters such as effect of pH (2–8), contact time (5–120 min), initial Cd 2+ concentration (25–200 mg L −1 ), and temperature (25–40°C). The equilibrium was established within 90 min where 82% Cd 2+ was adsorbed using YVO4 :Eu 3+ nanoparticles. Kinetic studies showed better applicability for pseudo-second-order model. Langmuir and Freundlich isotherm models were employed for fitting the equilibrium data, and it was found that the Langmuir model fitted the data better than the Freundlich model.